Early education curriculum a child's connection to the world - Beaver, Nancy H.; Wyatt, Susan; Jackman, Hilda L. (Australia Cengage Learning, 2018)
"Early Education Curriculum: A Child's Connection to the World shows you how to conduct observations and assessments of children and the program, plan and implement a curriculum, set up an inclusive child-centered environment, and evaluate and document program quality and children's learning. Whether you are a student or an experienced teacher, this book will help you learn how to make informed decisions about curriculum content as well as to develop creative thinking skills and effectively apply theory to an early childhood classroom setting. Updated with the most current research and standards, the seventh edition presents new material on brain research that underlies teaching ideas as well as new information on reflective practice, intentional teaching, and using the environment as a teaching tool. Case studies allow you to apply your knowledge to solve real-life dilemmas. The book's strong applied approach focuses on the how-to's of teaching, with many hands-on teaching tips"--Provided by publisher.
Previous editions entered under Jackman, Hilda.
Keywords: Early childhood education -- Curricula -- United States; Curriculum planning -- United States; Interdisciplinary approach in education -- United States; Early childhood education -- Activity programs -- United States